An improvised indexing technique for XML data over multiple channels in wireless environment: (1, Xm) method. (5th August 2019) - Goel, Vikas; Gautam, Deepali; Gupta, Amit; Kumar, Sachin
Summary: Wireless broadcasting is the new emerging standard for disseminating the information. It also exploits the feature of mobile computing environment, i.e., an asymmetric environment where the bandwidth of downloading is much higher than the bandwidth of uploading. Due to the small devices, created to hold the feature of portability, various difficulties are imposed on the system. The mobile client follows some energy restricted traits to be efficient. Those traits are access time and tuning time. Access time basically tells the efficiency of the system by specifying how fast a user may get data. But tuning time measures the battery life of the device. In this paper, we have proposed (1, Xm ) method to deal with these. Here, Xm basically implies the XML data passing on to the multiple channels. In this technique, we have sent data by indexing onto two different channels: index and data channel. We have analyzed the performance of the proposed indexing technique. To prove its validity, the improved results are compared with the former indexing techniques analytically and experimentally. Abstract : The proposed (1, Xm ) technique utilizes multiple channels in a wireless broadcasting environment. The index and data are broadcasted on the different channels. To show the efficiency and effectiveness of the proposed technique, experimental results are analyzed and depicted.